Commuting Patterns and Health Problems of Commuters in Regional Tourist Destination (Case Study in Denpasar Greater Area) - Milla Herdayati; Tris Eryando (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Commuting has become a global phenomenon in various metropolitan cities in the world, including Denpasar. Denpasar is the center of tourist destinations for Indonesian and foreign tourists. This condition makes Denpasar a business and economic center for residents in the surrounding area. Conditions have encouraged an increasing number of commuter workers in Denpasar from sub-urban areas. The people are facing several problems such as traffic, air, noise, thermal pollution, and long duration of commuting. This study aims to analyze the relationship between commuting patterns and health problems among workers in Denpasar metropolitan areas in Indonesia. This study analyzed by using secondary data of the Sarbagita (Denpasar, Badung, Gianyar, and Tabanan) Commuter Survey 2015 from CBS Indonesia. Sample study: commuter workers aged 15-65 years with inclusion criteria are commuters passive commuting with all types of transportation except bicycles/walking. The sampling method used two stages of cluster sampling. The final sample was 652 persons. Statistical analysis used binary logistic regression. The study shows that around one-third of commuters have commuting-related health problems. Health problems are more perceived by formal workers, low incomes, and low-educated. This study shows that distance and transportation mode had correlated with health problems (OR=1.71). Motorcycle and private car users have more health problems than public transportation (OR=2.49; OR=3.13). The impact of commuting for com-muter health can be minimized by providing public transportation that is fast, safe, comfortable, and inexpensive. Local government must encourage the use of public transportation for commuters through campaigns from a public health perspective.